2014
DOI: 10.1021/am502208g
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Three-Dimensional Graphene Foam/Poly(dimethylsiloxane) Composites and Their Potential Application as Strain Sensor

Abstract: A three-dimensional (3D) graphene foam (GF)/poly(dimethylsiloxane) (PDMS) composite was fabricated by infiltrating PDMS into 3D GF, which was synthesized by chemical vapor deposition (CVD) with nickel foam as template. The electrical properties of the GF/PDMS composite under bending stress were investigated, indicating the resistance of the GF/PDMS composite was increased with the bending curvature. To improve the bending sensitivity of the GF/PDMS composite, a thin layer of poly(ethylene terephthalate) (PET) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 38 publications
0
100
2
Order By: Relevance
“…Importantly, compared with other strategies to construct percolation networks, such as CVD, template‐assisted approach, and filling microchannel with liquid metals, our approach is based on solution‐processable graphene at room and mild conditions, and it can be readily scaled up. Although GS has been prepared by CVD or template‐assisted approaches, CVD is high‐cost and time‐consuming, while template‐assisted approach requires complex etching processes to eliminate templates. The sol–gel approach in our work is significantly advantageous than the previous methods in terms of fabrication complexity, production costs, and scalability.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, compared with other strategies to construct percolation networks, such as CVD, template‐assisted approach, and filling microchannel with liquid metals, our approach is based on solution‐processable graphene at room and mild conditions, and it can be readily scaled up. Although GS has been prepared by CVD or template‐assisted approaches, CVD is high‐cost and time‐consuming, while template‐assisted approach requires complex etching processes to eliminate templates. The sol–gel approach in our work is significantly advantageous than the previous methods in terms of fabrication complexity, production costs, and scalability.…”
Section: Resultsmentioning
confidence: 99%
“…Ni foam was used to catalyze the graphene growth [20]. First, the nickel foam was cut to a desired size.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies [20], only the static bending and tensile test signal is reported. The piezo-resistive stain sensors mostly detect signal by mechanical stimuli owing to its sensing mechanism based on the change in resistance due to mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the templates need to be removed to leave porous 3D GSs for applications in flexible energy‐storage devices and strain sensors. CVD is another common method for the synthesis of high‐quality GSs that exhibit high conductivity, but this technique it is time‐consuming, costly, and leads to uncontrolled pore sizes . Different from these methods, the self‐assembly process usually starts from graphene oxide (GO), which combines the many oxygen‐containing groups on the surface of the GO sheet.…”
Section: Introductionmentioning
confidence: 99%